An Iterative Algorithm for Approximating Solutions of Hammerstein Equations with Bounded Generalized Phi-Monotone Mappings. (11th March 2020) - Chidume, C. E.; Bello, A. U.
Abstract: Let E = L p, 1 < p < ∞ and E * denote its dual space. Let F : E → E * and K : E * → E be bounded generalized Φ 1 -strongly, and Φ 2 -strongly monotone maps, respectively. Suppose the Hammerstein equation u + K F u = 0 has a solution u * in E . An iteration sequence is constructed and proved to converge strongly to u *. Our technique of proof is also of independent interest.